CHRISTOPHORUS CLP 73,327. Christi Geburt in der Liturgie der Äthiopier (The Birth of Christ in the Liturgy of the Ethiopians). 10" 33? r.p.m. mono record. Price: DM 15,-. (International Library of African Music, 1968)
pages: 65
Keywords: African Music; Ethiopia